2017
DOI: 10.1007/s00234-017-1840-0
|View full text |Cite
|
Sign up to set email alerts
|

Lesion location associated with balance recovery and gait velocity change after rehabilitation in stroke patients

Abstract: Initial balance function as well as the interval between stroke onset and the initiation of therapy might influence balance recovery and gait velocity changes. Damage to the insula and internal capsule also affected gait velocity change after rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
2
11
0
3
Order By: Relevance
“…Many researchers report that the outcomes of conducted therapy are independent of age and sex [24][25][26]. The results of the present study confirm this observation.…”
Section: Discussionsupporting
confidence: 90%
“…Many researchers report that the outcomes of conducted therapy are independent of age and sex [24][25][26]. The results of the present study confirm this observation.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with these previous studies, the present study also revealed that age, hematoma volume, and neurological severity, as measured with the NIHSS, were related to independent walking in patients with thalamic hemorrhage. Reports from rehabilitation hospitals show that there is a strong relationship between an improved functional outcome at rehabilitation hospital discharge and the early initiation of rehabilitation services [ 12 , 13 ]. Since no information on the rehabilitation interventions performed at the acute-care hospital was available in this study, this factor should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moon и соавт. [15], в котором не было выявлено различий в изменении скорости ходьбы и сохранении равновесия между группами с супра-и субтенториальной локализацией инсульта. Различия, с одной стороны, могут быть объяснены достоверно более выраженными двигательными нарушениями в исследовании Н.…”
Section: заключениеunclassified
“…[15]. Средний балл по шкале FIM при поступлении и при выписке со-ставил 57±24/72±30 [15], в нашем исследовании -118±6/122±4 соответственно, t>5,42, p=0,000. Необходимо отметить, что выраженные двигательные расстройства могут маскировать нарушения равновесия.…”
Section: заключениеunclassified
See 1 more Smart Citation